Oceanic anoxic events of the Cretaceous period and their role in the formation of source rocks in the basins of continental margins - A.I. Konyukhov (Georesursy, 2017)
The Cretaceous period was marked not only by the dominance of warm climate, vast transgressions of the sea and widespread occurrence of carbonate deposits, but also by the formation of the richest petroleum formations, which are associated with the generation of a huge amount of hydrocarbons in the largest oil and gas basins of modern continental margins. Both early and late Cretaceous epochs were marked by several oceanic anoxic events (OAE) of global and regional scale, accompanied by the accumulation of sediments enriched in organic matter, and by significant shifts in the ratios of stable isotopes C, O, and Sr. Various aspects of these events are considered in a huge number of articles published in recent years in major scientific publications. Unfortunately, their role in the formation of oil reservoirs has remained outside the scope of scientific analysis. Meanwhile Cretaceous OAE’s had led to the spreading of black shale and other sediments with high content of organic matter on the floor of Tethys ocean, central part of Atlantic and on the seamounts in the Pacific ocean. Among them only OAE 1a (Selli) and OAE 2 (Bonarelli) are known as more large anoxic events. The first occurred in the middle of Aptian time, the second near the Cenomanian-Turonian boundary (CTB). The analysis of the spreading of source rocks in the largest oil-and-gas bearing basins on the continental margins at that time – the Persian Gulf, Maracaibo, Middle and Upper Magdalena river, Putumayo and other basins – showed that episodes of OAE’s had not always found a reflection in the succession of major source rock’s formations. In the Persian Gulf a list of source rocks includes Hanifa, Garau, Gadvan, Kazhdumi, Ahmadi member and Gurpi formations of Cretaceous age. Thus it is certain that OAE’s were only separate parts of more complex history of accumulation of black shale and carbonate deposits with high content of total organic carbon on the continental margins of the Cretaceous time.